Phonetic challenges in EFL classrooms: digraphs in a second-chance school context, an exploratory study - Caro Araya, Gonzalo Manuel (Universidad de Santiago de Chile, 2023)
Integrantes: Gonzalo Caro, Valentina Macías, Valentina Salazar, Cristian Sotelo
Keywords: Inglés - Enseñanza - Hablantes extranjeros; Inglés - Pronunciación para hablantes extranjeros - Enseñanza; Deserción escolar